(untitled) (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2017)
This paper explores the rhetoric of political repression in the Guardian newspaper reports of June and July 2008 Nigerian Union of Teachersâ€Ÿ (NUT) nationwide strike embarked upon to demand a special salary scale. It specifically focuses on language use in the newspaper reports on this issue as an indication of the media’s seemingly transparent but inherently ideological reportage, projecting the â€œtruthâ€ of the political power elite and repressing the views of the less dominant whose interest the media supposedly champion. Using three theoretical perspectives, critical discourse analysis which takes the side of the less privileged to question the textual representations of the power elite; systemic functional grammar which studies the meaning relations residing in the systemic patterns of textual choices of language users; and argumentation theory used to determine the various appeals made in the reports to argue the case of the various stakeholders, the paper highlights the truism of the mediaâ€Ÿs apparent neutrality in their reports. The various forms of rhetoric, located in the unsaid, attribution to sources, manipulation of intertextual resources and gatekeeping ideology were among the strategies employed in the newspaper reportage. In a total of forty-six reports, spanning thirty-six days the strike lasted,it was found that the newspaper deliberately avoided an editorial on the strike thereby locating its ideology in the â€žunsaidâ€Ÿ. It also, in connivance with the dominant power elite, manipulated the wordings of the Constitution of the Federal Republic of Nigeria 1999 using ad hoc argument and subtle persuasion to quash the demands of the NUT, thus exploiting intertextual resources (â€žthe already-saidâ€Ÿ) to support a suppressive regime. These representations portray the newspaperâ€Ÿs gate keeping-ideology â€“as partial and selective in its reports. It also implicates the newspaper as adopting the â€žideology of silenceâ€Ÿ and as reneging on its watchdog role as the champion of public interest.